Distinctive Feature of Microbial Communities and Bacterial Functional Profiles in Tricholoma matsutake Dominant Soil. - Seung-Yoon Oh; Jonathan J Fong; Myung Soo Park; Young Woon Lim (PLoS ONE, 2016)
Tricholoma matsutake, the pine mushroom, is a valuable forest product with high economic value in Asia, and plays an important ecological role as an ectomycorrhizal fungus. Around the host tree, T. matsutake hyphae generate a distinctive soil aggregating environment called a fairy ring, where fruiting bodies form. Because T. matsutake hyphae dominate the soil near the fairy ring, this species has the potential to influence the microbial community. To explore the influence of T. matsutake on the microbial communities, we compared the microbial community and predicted bacterial function between two different soil types-T. matsutake dominant and T. matsutake minor. DNA sequence analyses showed that fungal and bacterial diversity were lower in the T. matsutake dominant soil compared to T. matsutake minor soil. Some microbial taxa were significantly more common in the T. matsutake dominant soil across geographic locations, many of which were previously identified as mycophillic or mycorrhiza helper bacteria. Between the two soil types, the predicted bacterial functional profiles (using PICRUSt) had significantly distinct KEGG modules. Modules for amino acid uptake, carbohydrate metabolism, and the type III secretion system were higher in the T. matsutake dominant soil than in the T. matsutake minor soil. Overall, similar microbial diversity, community structure, and bacterial functional profiles of the T. matsutake dominant soil across geographic locations suggest that T. matsutake may generate a dominance effect.